A scalable realization of local U(1) gauge invariance in cold atomic mixtures - Mil, Alexander; Zache, Torsten Victor; Hegde, Apoorva Anant; Xia, Andy Xiyuan; Bhatt, Rohit Prasad; Oberthaler, Markus K.; Hauke, Philipp; Berges, Jürgen; Jendrzejewski, Fred (Science, 2020)
Gauge invariance with cold atoms - There is considerable interest in developing quantum computational technologies that can simulate a series of physical phenomena inaccessible by classical computers. Mil et al. propose a modular scheme for quantum simulation of a U(1) lattice gauge theory based on heteronuclear spin-changing collisions in a mixture of two bosonic quantum gases isolated in single wells of a one-dimensional optical lattice. They engineered the elementary building block for a single well and demonstrate its reliable operation that preserves the gauge invariance. The potential for scalability of the proposed scheme opens up opportunities to address challenges in quantum simulating the continuum limit of the gauge theories. - Science, this issue p. 1128 - In the fundamental laws of physics, gauge fields mediate the interaction between charged particles. An example is the quantum theory of electrons interacting with the electromagnetic field, based on U(1) gauge symmetry. Solving such gauge theories is in general a hard problem for classical computational techniques. Although quantum computers suggest a way forward, large-scale digital quantum devices for complex simulations are difficult to build. We propose a scalable analog quantum simulator of a U(1) gauge theory in one spatial dimension. Using interspecies spin-changing collisions in an atomic mixture, we achieve gauge-invariant interactions between matter and gauge fields with spin- and species-independent trapping potentials. We experimentally realize the elementary building block as a key step toward a platform for quantum simulations of continuous gauge theories. - Tunable spin-changing collisions in cold atomic mixtures can be used to implement scalable gauge-invariant dynamics. - Tunable spin-changing collisions in cold atomic mixtures can be used to implement scalable gauge-invariant dynamics.
Gesehen am 14.04.2020